2018
DOI: 10.3389/fnmol.2018.00334
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine Released During Traumatic Events May Strengthen Contextual Fear Memory Through Increased Hippocampus mRNA Expression of Nr4a Transcription Factors

Abstract: Epinephrine (EPI) strengthens contextual fear memories by acting on peripheral β2-adrenoceptors. Phenylethanolamine-N-methyltransferase-knockout (Pnmt-KO) mice are EPI-deficient mice and have reduced contextual fear learning. Our aim was to evaluate the molecular mechanisms by which peripheral EPI strengthens contextual fear memory and if a β2-adrenoceptor antagonist can erase contextual fear memories. Pnmt-KO and wild-type (WT) mice were submitted to fear conditioning (FC) procedure after treatment with EPI, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 49 publications
(63 reference statements)
2
36
0
Order By: Relevance
“…Previous studies showed Nr4a subfamily genes expression in the hippocampus to be upregulated after training of fear conditioning procedure contributing to contextual memory consolidation on the next day (von Hertzen and Giese, 2005;Hawk and Abel, 2011;Hawk et al, 2012). Also, we have already shown that glucose may be a mediator of EPI in the central nervous system and could be important to induce the expression of the Nr4a family genes involved in contextual fear memories (Oliveira et al, 2018). The NR4A transcription factors induce the expression of several target genes, such as the brain-derived neurotrophic factor (Bdnf ) gene suggested to play an important role in hippocampus-dependent contextual fear memory (Mizuno et al, 2012).…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Previous studies showed Nr4a subfamily genes expression in the hippocampus to be upregulated after training of fear conditioning procedure contributing to contextual memory consolidation on the next day (von Hertzen and Giese, 2005;Hawk and Abel, 2011;Hawk et al, 2012). Also, we have already shown that glucose may be a mediator of EPI in the central nervous system and could be important to induce the expression of the Nr4a family genes involved in contextual fear memories (Oliveira et al, 2018). The NR4A transcription factors induce the expression of several target genes, such as the brain-derived neurotrophic factor (Bdnf ) gene suggested to play an important role in hippocampus-dependent contextual fear memory (Mizuno et al, 2012).…”
Section: Discussionmentioning
confidence: 63%
“…We have already suggested that after a fear event, EPI is released from the adrenal gland to the bloodstream. Afterward, EPI may act in β 2 -adrenoceptors inducing liver cells to release a transient glucose surge into the blood which may be a mediator in the central nervous system strengthening contextual fear memories (Alves et al, 2016;Oliveira et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This response is important for survival and adaptation in nature. Epinephrine may induce liver cells to release glucose into the bloodstream and glucose may lead to a subsequent increase of the energy source in the central nervous system and enhance contextual fear learning [23] . Studies have shown that the amygdala is critical to fear responses and emotional memory.…”
Section: Fearmentioning
confidence: 99%